Predictores de la eficacia de recepción en voleibol mundial masculino U-21 y absoluto - González-Silva, J.; Fernández-Echeverría, C.; Conejero, M.; Moreno, M. P. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2021)
The aim of the study was to understand which variables of the reception action predict reception efficacy in two different competition categories (U-21, absolute) in male volleyball. The study sample comprised 3,442 serve-reception actions: 1,894 performed by players in U-21 category (U-21 Men´s World Championship) and 1,548 performed by players in senior category (senior Men`s World Championship). The variables considered as predictors were: receiver player, previous displacement of the receiver, type of reception, receiver position, reception technique reception zone. Logistic regression analysis showed that previous displacement of the receiver and reception technique were predictors of reception efficacy in both categories, U-21 and senior. Type of reception and reception zone were predictors of efficacy in the U-21 category, but not the senior category. Receiver position was predictive of efficacy uniquely for the senior. These may benefit the training process by favouring the design of specific tasks for each level of play.